INTEGRATING PEACE EDUCATION INTO THE NIGERIAN BASIC EDUCATION CURRICULUM FOR A LASTING PEACE AND ENVIRONMENTAL SUSTAINABILITY - Ofojebe, Fr. (European Scientific Journal, ESJ, 2014)
This study examined the essentials of integrating peace education into the Nigerian Basic Education curriculum for a lasting culture of peace and environmental sustainability. The study also identified need for teaching peace education at the basic education level in order to inculcate in the child the rightful spirit, awareness and consciousness to protect their environment owing to the recent turbulent crisis/challenges facing the Nigeria society. Three research questions and three hypotheses guided the study. The descriptive survey research design was employed in the study in order to collect data. Simple random sampling was used to select 783 head teachers, while stratified proportionate sampling technique was used to select 800 teachers. A questionnaire titled: â€œParticipants Responses on Integrating Peace Education into Basic Education Curriculum for Peace and Environmental Sustainability Questionnaireâ€, (PRIPEBECPESQ) containing 40 items and drawn on a 4-point rating scale was used for data collection. Validity and reliability of the research instrument was also determined. Data was analyzed using frequency distribution, mean rating and standard deviation. The Z-score statistics was used to analyze the hypotheses at 0.05 level of significance. From the findings of the study, recommendations were proffered and among such included that there should be new reforms in the basic education curriculum which should be highly propagated by effective implementation and adequate funding/financing of basic education in Nigeria. School administrators and teachers should be trained professionally for effective implementation of this course at the classroom level.